1999
DOI: 10.1093/jmedent/36.3.263
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Infestation by AdultDermacentor variabilis(Acari: Ixodidae) in a Mark-Recapture Study of Raccoons (Mammalia: Carnivora) and Virginia Opossums (Mammalia: Didelphimorphia) in Tennessee

Abstract: A mark-recapture study of raccoons (Procyon lotor L.) and Virginia opossums (Didelphis virginiana Kerr) was conducted from February 1991 through April 1994 to determine host interactions with adult Dermacentor variabilis Say. We captured 1,293 raccoons and Virginia opossums during the 3-yr study (140 individual raccoons and 160 individual Virginia opossums) with 1,895 adult D. variabilis collected. Raccoons had a significantly higher mean intensity and higher prevalence of adult ticks than Virginia opossums (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
2
4
1
Order By: Relevance
“…Observed variation in monthly prevalence of tick infestation agreed with previous reports on seasonal activity of ticks in different parts of the country (Anderson and Magnarelli 1980, Barker et al 2004, Carey et al 1980, Kardatzke et al1992, Koch 1982, Kollars and Ladine 1999, Stafford and Magnarelli 1993. For example, D. variabilis parasitized a significantly higher percentage of raccoons and opossums in Tennessee from April through September than from October through March (Kollars and Ladine 1999).…”
Section: Canine Tick Infestation In the United States 2002-2004 71supporting
confidence: 90%
See 3 more Smart Citations
“…Observed variation in monthly prevalence of tick infestation agreed with previous reports on seasonal activity of ticks in different parts of the country (Anderson and Magnarelli 1980, Barker et al 2004, Carey et al 1980, Kardatzke et al1992, Koch 1982, Kollars and Ladine 1999, Stafford and Magnarelli 1993. For example, D. variabilis parasitized a significantly higher percentage of raccoons and opossums in Tennessee from April through September than from October through March (Kollars and Ladine 1999).…”
Section: Canine Tick Infestation In the United States 2002-2004 71supporting
confidence: 90%
“…For example, D. variabilis parasitized a significantly higher percentage of raccoons and opossums in Tennessee from April through September than from October through March (Kollars and Ladine 1999). In the present study, tick prevalence was highest in Tennessee from April through August.…”
Section: Canine Tick Infestation In the United States 2002-2004 71contrasting
confidence: 41%
See 2 more Smart Citations
“…However, opossums may become the principal host when its populations are dense (Zimmerman et al 1988). In Tennessee, raccoons become infested 2.77 times more quickly by adult D. variabilis than do opossums (Kollars and Ladine 1999). In the current study we found that opossums and raccoon serve as hosts to spotted fever group Rickettsia infected adult D. variabilis in western Tennessee.…”
Section: Resultssupporting
confidence: 49%